2022
DOI: 10.1108/imefm-09-2021-0358
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and risk dynamics of financial markets in G7 countries

Abstract: Purpose The purpose of this study is twofold: to examine the effects of the COVID-19 pandemic on the risk dynamics of stock and bond markets in G7 countries; and to examine if the stock-bond risk dynamics can be linked to government measures to contain the pandemic. Design/methodology/approach To examine the pandemic impact on the risk dynamics of the bond and stock markets, this study chooses G7 countries for their efficient financial market properties. This study uses standard generalized autoregressive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(60 reference statements)
0
4
0
1
Order By: Relevance
“…A wide range of marketbased indicators can help measure financial market participants' assessment of the economy and current conditions to inform decisions about changes in financial policy settings (Muzi et al, 2022). Ensure transparency and information that can be used by market participants to assess the viability of the company (Mobin, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of marketbased indicators can help measure financial market participants' assessment of the economy and current conditions to inform decisions about changes in financial policy settings (Muzi et al, 2022). Ensure transparency and information that can be used by market participants to assess the viability of the company (Mobin, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Now, as policy space is constrained and firms and people have reduced financial buffers, COVID-19-related vulnerabilities may materialize. Moreover, the uneven global recovery increases the likelihood of negative spillovers (Mobin, 2022). And vulnerabilities that support mechanisms to prevent COVID-19 may now materialize.…”
Section: Introductionmentioning
confidence: 99%
“…Wabah Covid-19 memiliki dampak yang kuat terhadap volatilitas harga saham perbankan pada Kawasan Eropa, dan volatilitas meningkat selama Pandemi Covid-19 (Foglia et al, 2022). Pandemi Covid-19 juga menyebabkan volatilitas yang lebih tinggi pada pasar modal negara-negara yang tergabung dalam Kelompok G7, dimana pasar saham dan obligasi di Canada memiliki volatilitas yang paling tinggi, sementara di Italia merupakan yang paling sensitif, Jepang menunjukkan persistensi tertinggi (Mobin et al, 2022).…”
Section: Pendahuluanunclassified
“…Recently, extant studies (Krieger et al , 2021; Cejnek et al , 2021) have revealed high dividend cuts and omission rates during COVID-19. This is unsurprising due to the well-documented adverse effect of COVID-19 on various aspects of stock markets in general and corporate performance in particular (Ashraf, 2020; Harjoto and Rossi, 2021; Scherf et al , 2022; Mobin et al , 2022; Rahman et al , 2022). Nevertheless, most firms could either maintain or even increase their dividends during the pandemic to maintain more stable dividend policies in response to the crisis and signal their financial prospect (Mazur et al , 2020; Ali, 2022).…”
Section: Introductionmentioning
confidence: 99%